Reduction Of Backscattered Radiation For X-Ray Image Quality Enhancement - Qaed Naji, Abdullah Taher (2016)
This study mainly aims to reduce backscattered radiation inside an X-ray room. The characteristics of X-ray attenuation in several materials such as lead, copper, iron steel, aluminium, and concrete have been investigated under different exposure parameters to measure their abilities to attenuate incident X-ray and to reduce backscattered X-ray. Lead and Iron presented good attenuation values for incident X-ray at radiographic diagnosis energy range (50 -110 kVp), whereas iron and aluminium reflected the least amount of backscattered radiation dose. A number of anti-scatter grids have been designed and fabricated from iron steel and aluminium, because of their relatively better abilities to reduce backscattered radiation compared to other materials.